Sleep deprivation, stress and anxiety among pre-university college students of Mangaluru city, India - Nartiang, Durka; P., Jagannath (International Journal Of Community Medicine And Public Health, 2019)
Background: Adequate sleep is extremely important for appropriate physical growth, emotional stability, behavior, and maintenance of cognitive function. Good quality of night sleep will reflect in better school performance and increased motivation to study. The aim of this study is to determine the level of sleep deprivation, daytime sleepiness, stress and anxiety and to associate stress, anxiety with sleep pattern. Methods: A college based, cross-sectional study was conducted in Mangaluru City, Karnataka. The study has been conducted among 5 pre–university colleges (2 from Aided, 2 from private and 1 from government). A total of 634 participants were enrolled from grade 11th and 12th irrespective of their stream and responded to a questionnaire that included socio-demographic characteristics, sleep pattern, daytime sleepiness by using Epworth sleepiness scale, level of stress using Perceived stress scale-10, level of examination anxiety and general anxiety by using Westside Anxiety scale and Anxiety Self-Rating scale. Descriptive statistics, chi square or likelihood ratio test were used. The data was entered and analysed using SPSS 16v. Results: Among 634 students the mean age was found to be 16 years. Prevalence of sleep deprivation was found to be 39%, daytime sleepiness was 66.6%, 77.8% had moderate stress and 9.1% had high stress. Moderately high-test anxiety was observed among 22.6% of the respondents and 1.4% with extreme anxiety. Conclusions: The study showed that 1/3rd of the respondents had sleep deprivation and 2/3rd had daytime sleepiness and the prevalence of general anxiety was higher than examination anxiety and most of the respondents had moderate stress.